Adapting Transformative Leadership in Islamic Education: Insights from Madrasah - Nifasri, Nifasri (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the implementation of transformative leadership in madrasahs, focusing on four main components: idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. This study uses a qualitative approach with a case study design. Data collection techniques are carried out through interviews, observations and documentation. The data obtained are then analyzed using thematic analysis techniques to identify patterns related to implementing transformative leadership. The study results indicate that the madrasah principal successfully acts as a role model that inspires motivates, and supports innovation among teachers and students. Implementing this transformative leadership improves the quality of education by balancing academic achievement and character development of students. However, this study also identified several limitations, such as the lack of active participation in decision-making and suboptimal support for intellectual stimulation. This study provides important implications for leadership development in madrasahs, namely the need to increase the active participation of teachers and students in decision-making and more optimal support for intellectual stimulation. Implementing more inclusive transformative leadership can improve the quality of education, both in terms of academics and the character development of students.